Assessing environmental knowledge of High School students on mangrove’s role in climate change mitigation: A case study in the Mahakam Delta - Novia Dwi Iriyanti; Pintaka Kusumaningtyas; Muhammad Amir Masruhim; Puji Windi Astuti; Nisa Ul Khoiriyyah (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2025)
Mangrove ecosystems play an important role in climate change mitigation through their ability to absorb and store carbon. Students' knowledge about this needs to be improved to support students' environmental awareness. This study aims to measure the level of environmental knowledge of grade XI students in the Mahakam Delta region about the role of mangroves in mitigating climate change. The research method used a quantitative descriptive method, with data collection through written tests. The results showed that the average environmental knowledge of students was 61.62 with a sufficient category. The results of the frequency distribution of students show 38% of students have environmental knowledge in the good category, 36% are in the sufficient category, 11% are in the less category, and 15% are in the very less category. Although most students have environmental knowledge in the good category, there are no students who reach the excellent category, and 71% are still below the good category. Therefore, efforts are needed to improve students' environmental knowledge, especially through integration into science/chemistry learning.